The measurement of the atmospheric minor constituents by infrared spectroscopy (abstract) - Muramatsu, Hisafumi; Makino, Yukio; Hirota, Michio; Sasaki, Tohru; Kawaguchi, Sadao; Yamanouchi, Takashi (1983)
P(論文) departmental bulletin paper